Food Safety and Halal Certification Seminar Towards Mandatory Halal Food in October 2024 - Hanie Kusuma Wardani; Wahyu Kusuma Wardani (Universitas STRADA Indonesia, 2024)
Food safety and halal certification are important aspects of the food industry in Indonesia, especially ahead of the mandatory halal certification in October 2024. This seminar aims to increase the understanding of food business actors about the importance of producing safe and halal food, as well as providing information about the process and requirements of halal certification. The methods used are seminars and interactive discussions organized by the collegiate association of Senior High School 2 Kediri (Ikasmada) on March 30, 2024. This seminar was attended by 39 collegiate who have businesses in the food sector and other. The results of the seminar showed an increase in participants' understanding of food safety regulations, the process of applying for a home industry product distribution permit, and self-declare halal certification. Interactive discussions generated questions about halal certification regulators, technical applications for home industry product distribution permit and halal certification, and suggestions for programs related to micro small business and food safety. In conclusion, this seminar is useful in providing insight and motivating food businesses actors to take care of licensing and halal certification to support government programs towards mandatory halal food in October 2024.